The Bloomsbury handbook of sonic methodologies - Bull, Michael 1952-; Cobussen, Marcel 1962- (Bloomsbury Academic, 2021)
An interdisciplinary overview of the variety of sonic methodologies used by sound scholars and artists based on contemporary theories and empirical analyses"--